VITAMIN D LEVELS AND VDR rs2228570 GENETIC VARIANT IN AUTOIMMUNE THYROIDITIS - Parveen Shaikh , Aleena; Parveen Shaikh , Nameera; Nakashidze, Irina (Sanamed, 2023)
Autoimmune Thyroiditis (AIT) is a prevalent autoimmune disorder characterized by an immune response targeting the thyroid gland. Genetic factors play a significant role in AIT susceptibility, with immune-related genes, especially the vitamin D receptor (VDR) gene, potentially influencing AIT development. This comprehensive review delves into the intricate association between VDR gene polymorphisms, particularly rs2228570 (FokI), and AIT susceptibility, exploring various populations. Research has unveiled contrasting outcomes regarding the link between the VDR rs2228570 polymorphism and AIT risk across diverse ethnic groups. Certain populations have exhibited a noteworthy correlation, suggesting that population-specific genetic factors contribute to AIT risk. A recurring observation of vitamin D deficiency in AIT patients has correlated with elevated anti-thyroid antibodies, abnormal thyroid function, and thyroid volume. The results emphasize the possible role of vitamin D in the development of AIT, suggesting the importance of vitamin D supplementation to address deficiencies associated with AIT. In addition to VDR rs2228570, other genetic variants have also shown associations with AIT susceptibility, displaying varying results across different populations. Ethnicity emerges as a pivotal factor influencing these associations, underscoring the need to consider genetic variations in diverse populations. We emphasize the intricate interplay between VDR gene polymorphisms, vitamin D, and AIT susceptibility. Extensive research is essential to unveil the clinical significance of these genetic variations, offering prospects for enhanced diagnostic and therapeutic strategies for individuals with AIT.